Direct Address Valence of Intransitive Verbs in Modern Armenian - Khachatryan, Gurgen; Grkikyan, Lala (Bulletin of Yerevan University B: Philology, 2023)
The article explores the compatibility possibilities of intransitive verbs in the Modern Armenian language.The study of the compatibility possibilities of intransitive verbs of Modern Armenian shows that in addition to subject, predicative, object and adverbial modifier, these verbs also combine with direct address, the expression of the valency of which is manifested only in the sentence. The fact is that the ability of a verb to accept direct address  is directly related to the grammatical act of predicativity. Only finite verbs can take direct address, or this happens with their obligatory participation and only in direct speech. But not all intransitive verbs accept direct address. An essential role in this is played by the fact to which class of words denoting an object the action expressed by this or that verb can belong.Only personal intransitive verbs can take direct address, however, the ability to accept direct address is characteristic of those intransitive verbs that are mainly combined with nouns denoting a person. Most of the latter can be combined with direct address both the singular and the plural, and only a limited number of the verbs accept the direct address  either only in the singular or only in the plural. Personal verbs that accept direct address  have limited compatibility: not all forms of these verbs accept direct address , but only the forms of the 2nd person singular and plural.The purpose of this research  is to study the vocative valency of intransitive verbs in Modern Armenian, the topic that  has not yet been explored. The study will provide an opportunity to form a more complete picture of the compatibility possibilities, i.e. the valency of intransitive verbs in the Modern Armenian language,  which determines the relevance of our study.
Keywords: Valency; ncyintransitive verbs; agreement; verbs combining; wit nouns; dtnoting a person; an object; an animal; collocabilit